Developing our students’ level of mindfulness during these unprecedented times - Reilly, Peter (Journal of University Teaching and Learning Practice, 2020)
The pandemic has provoked disruptions in students’ lives and studies worldwide, which has caused them to feel moderate to high levels of anxiety and stress. Universities have responded by offering online counseling and communicating self-help recommendations via their websites. Curiously, the role that professors could play to reduce this emotional hardship has been ignored in the literature. This instructional paper describes how and why three professors in Mexico include a brief, daily mindful practice in class to help their students cope with the negative emotions that may arise. Psychological and educational research has indicated that the development of mindfulness reduces emotional pain and increases one’s sense of well-being. Importantly, the focused-attention meditation described herein does not require an experienced mediator. A script to guide the practice is being used by the three professors, and could serve as a starting point for willing professors. Educators may also discover that the practice improves academic achievement because it activates executive functions (e.g. inhibitory control; working memory), thereby enhancing cognitive functioning. The paper also presents several practical implications involved with the practice, as well as initial reactions from professors and students.